Inhibition of CXCR4 and CXCR7 Is Protective in Acute Peritoneal Inflammation - Ngamsri, Kristian-Christos; Jans, Christoph; Putri, Rizki A.; Schindler, Katharina; Gamper-Tsigaras, Jutta; Eggstein, Claudia; Köhler, David; Konrad, Franziska M. (Frontiers in Immunology, 2020)
Our previous studies revealed a pivotal role of the chemokine stromal cell-derived factor (SDF)-1 and its receptors CXCR4 and CXCR7 on migratory behavior of polymorphonuclear granulocytes (PMNs) in pulmonary inflammation. Thereby, the SDF-1-CXCR4/CXCR7-axis was linked with adenosine signaling. However, the role of the SDF-1 receptors CXCR4 and CXCR7 in acute inflammatory peritonitis and peritonitis-related sepsis still remained unknown. The presented study provides new insight on the mechanism of a selective inhibition of CXCR4 (AMD3100) and CXCR7 (CCX771) in two models of peritonitis and peritonitis-related sepsis by injection of zymosan and fecal solution. We observed an increased expression of SDF-1, CXCR4 and CXCR7 in peritoneal tissue and various organs during acute inflammatory peritonitis. Selective inhibition of CXCR4 and CXCR7 reduced PMN accumulation in the peritoneal fluid and infiltration of neutrophils in lung and liver tissue in both models. Both inhibitors had no anti-inflammatory effects in A2B knockout animals (A2B-/-). AMD3100 and CCX771 treatment reduced capillary leakage and increased formation of tight junctions as a marker for microvascular permeability in wild type animals. In contrast, both inhibitors failed to improve capillary leakage in A2B-/- animals, highlighting the impact of the A2B-receptor in SDF-1 mediated signaling. After inflammation, the CXCR4 and CXCR7 antagonist induced an enhanced expression of the protective A2B adenosine receptor and an increased activation of cAMP (cyclic adenosine mono phosphate) response element-binding protein (CREB), as downstream signaling pathway of A2B. The CXCR4- and CXCR7-inhibitor reduced the release of cytokines in wild type animals via decreased intracellular phosphorylation of ERK and NFκB p65. In vitro, CXCR4 and CXCR7 antagonism diminished the chemokine release of human cells and increased cellular integrity by enhancing the expression of tight junctions. These protective effects were linked with functional A2B-receptor signaling, confirming our in vivo data. In conclusion, our study revealed new protective aspects of the pharmacological modulation of the SDF-1-CXCR4/CXCR7-axis during acute peritoneal inflammation in terms of the two hallmarks PMN migration and barrier integrity. Both anti-inflammatory effects were linked with functional adenosine A2B-receptor signaling.